EXAMINING THE MOTIVATION TO READ AND ITS RELATIONSHIP WITH SECOND LANGUAGE READING PROFICIENCY IN AN INDONESIAN EFL TERTIARY CONTEXT - Sahiruddin; Miftahul Jannah; Roosi Rusmawati (UIBU, 2022)
The purpose of this research is to investigate and describe the intrinsic and extrinsic motivations of tertiary-level EFL students in Indonesia toward reading English. Researchers used quantitative design in conducting this study. There were 77 students from English department at Universitas Brawijaya who voluntarily participate in this study, selected through convenience sampling. The quantitative method was applied by asking students to fill out a questionnaire adapted from Wigfield and Guthrie's Motivation for Reading Questionnaire (MRQ) (1997). Besides that, students’ self-assessment reading report used to measure students’ reading proficiency. In addition, The correlation between students' motivation to read and their reading proficiency was also investigated in this study. The data collected were analyzed using the SPSS program with descriptive statistics to answer research question 1 and Pearson correlation analysis to answer research question 2. The results indicated that students are relative highly extrinsic motivated in reading English. Meanwhile, both intrinsic and extrinsic motivation were found to have a significant correlation with students reading. In addition, it was also found that intrinsic motivation has the strongest correlation, and extrinsic motivation displayed lower correlation with reading proficiency. Based on these findings, lecturers are expected to increase students' intrinsic motivation to read.